Numerical Investigation of Deviation of Phase Change Characteristics of Horizontal and Vertical Flat Heat Pipe Configurations. (December 2015) - Hari, Rakesh; Jolly, Tom; Muraleedharan, C.
The flow characteristics in the porous wick of a flat heat pipe subjected to boiling and condensation are analysed here using two-phase mixture model. Steady laminar boundary layer flow in the capillary wick structure is considered for both vertical and horizontal orientations. The governing boundary layer partial differential equations are simplified using similarity transformation. The transformed equations are then solved numerically by using shooting iterative technique. Investigation was carried out for the effects of the involved parameters such as saturation and temperature across the boundary layer. The behaviour of non-dimensional numbers due to the orientation of the heat pipe is also discussed. The study confirms that orientation plays a significant role in flow and temperature field.